2015
DOI: 10.1371/journal.pone.0119095
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis and Major Quantitative Trait Locus Mapping of Leaf Widths at Different Positions in Multiple Populations

Abstract: BackgroundLeaf width is an important agricultural trait in maize. Leaf development is dependent on cell proliferation and expansion, and these processes exhibit polarity with respect to the longitudinal and transverse axes of the leaf. However, the molecular mechanism of the genetic control of seed vigor remains unknown in maize, and a better understanding of this mechanism is required.Methodology/Principal FindingsTo reveal the genetic architecture of leaf width, a comprehensive evaluation using four RIL popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…The present work identified three QTL for LL and six QTL for LW that were common across multiple populations or different generations in similar, or the same bins, as in previous studies (Tian et al 2011, Cai et al 2012, Ku et al 2012a, Guo et al 2015. Tian et al (2011) identified 36 QTL for LL and 34 QTL for LW in a genomewide association study of a maize nested association mapping population.…”
Section: Comparison Of Qtl Detected In the Ril And F 2:3 Populationssupporting
confidence: 79%
See 4 more Smart Citations
“…The present work identified three QTL for LL and six QTL for LW that were common across multiple populations or different generations in similar, or the same bins, as in previous studies (Tian et al 2011, Cai et al 2012, Ku et al 2012a, Guo et al 2015. Tian et al (2011) identified 36 QTL for LL and 34 QTL for LW in a genomewide association study of a maize nested association mapping population.…”
Section: Comparison Of Qtl Detected In the Ril And F 2:3 Populationssupporting
confidence: 79%
“…Guo et al. () identified eight mQTL for LWs at different positions above the uppermost ear in the four RIL populations in three environments, which included two QTL, qLW1 and qLW6‐2, detected in this study (Table ). Cai et al.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations